Interpreting Police Video: A Pilot Study. Issue 1 (13th October 2021) - Newell, Bryce Clayton
Abstract: The visual records police body‐worn cameras (BWCs) produce are frequently characterized as presenting more complete, comprehensive, and objective evidence of police‐public encounters than other forms of evidence. Despite a growing body of research on the social impacts of BWCs, we still lack a rich understanding of what information these technologies provide viewers. This ongoing exploratory project examines how people interpret what they see in BWC footage and what judgments they make about the appropriateness of depicted police conduct. Drawing from interviews with twelve students and twelve sworn police officers, I present initial exploratory findings. Participants viewed BWC video of a police‐public contact in which an officer stops a man on a sidewalk to question him, resulting in a foot chase and, ultimately, an arrest. When asked whether the officer's behavior was justified, police officer participants were more likely to focus on things like police training, procedure, and legality to justify the officer's action, while student participants were more likely to focus on the officer's demeanor, reporting that he should have been calmer and may have escalated the situation by not explaining clearly why he had initiated the stop.